2012
DOI: 10.1002/jssc.201200100
|View full text |Cite
|
Sign up to set email alerts
|

Methods for determination of polybrominated diphenyl ethers in environmental samples – review

Abstract: Polybrominated diphenyl ethers (PBDEs) are a group of persistent organic pollutants. They are used as flame retardants in plastics, paints, varnishes and textile materials. PBDEs pose great risk to the environment because of their high persistence and ability to get into the environment easily due to the lack of chemical bonds with the matrix of materials, to which they are added. Global research studies confirmed the occurrence of those compounds in the majority of elements of water and land environment. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…While NHANES may not be an entirely relevant comparison for newborns, the range of POP concentrations in NHANES approximately matched (factor of two) PCB, BFR and pesticide levels reported in several recent studies [52, 53]. Notably, pesticide exposures in some countries can considerably exceed levels found in the USA (as suggested by results for the six volunteers discussed earlier).…”
Section: Resultssupporting
confidence: 71%
“…While NHANES may not be an entirely relevant comparison for newborns, the range of POP concentrations in NHANES approximately matched (factor of two) PCB, BFR and pesticide levels reported in several recent studies [52, 53]. Notably, pesticide exposures in some countries can considerably exceed levels found in the USA (as suggested by results for the six volunteers discussed earlier).…”
Section: Resultssupporting
confidence: 71%
“…In these recent years, with the advent and popularity of chemical instrumentation, particular to mass spectrometry, various chromatographies coupled to mass spectrometry became the most sensitive and selective analytical tools for testing these types of compounds. Separate reviews on analyzing organochlorine pesticides (OCPs) in ambient air [4], dioxins and PBDEs in environmental samples [5], and perfluorinated compounds (with PFOS) [6,7] have also been published.…”
Section: Introductionmentioning
confidence: 99%
“…BFRs, in particular PBDEs, have been the FRs most widely studied, and different reviews on the analytical techniques used for the determination of these compounds in various matrices are available in the literature [67,68]. In general, a low amount of solid samples, 0.1-2 g, was employed in UAE, but it was reported that, in samples with low lipid content, the sample amount must be higher for better quantitation [68].…”
Section: Flame Retardants (Frs)mentioning
confidence: 99%